The Glycolytic Phenotype is Correlated with Aggressiveness and Poor Prognosis in Invasive Ductal Carcinomas - Jang, Se Min (Korean Breast Cancer Society, 2012)
PURPOSE: Glucose uptake and glycolytic metabolism are enhanced in cancer cells, and increased expression of glucose transporter 1 (GLUT1) has also been reported. The aim of this study was to investigate GLUT1 expression in human breast tissues and invasive ductal carcinomas. METHODS: We used tissue microarrays consisting of normal breast tissue, ductal hyperplasia, ductal carcinoma in situ, invasive ductal carcinoma, and lymph node metastases. We examined GLUT1 expression in the microarrays by immunohistochemistry, reviewed the medical records and performed a clinicopathological analysis. RESULTS: Membranous GLUT1 expression was observed in normal and tumor cells. GLUT1 expression was higher in ductal carcinoma in situ, invasive ductal carcinoma, and lymph node metastasis than in normal tissue and ductal hyperplasia (p=0.002). Of 276 invasive ductal carcinomas, 106 (38.4%) showed GLUT1 expression. GLUT1 expression was correlated with higher histologic grade (p<0.001), larger tumor size (p=0.025), absence of estrogen receptor (p<0.001), absence of progesterone receptor (p<0.001), and triple-negative phenotype (p<0.001). In univariate survival analysis, patients with GLUT1 expression had poorer overall survival and disease-free survival (p=0.017 and p=0.021, respectively, log-rank test). In multivariate survival analysis with the Cox proportional hazards model, GLUT1 expression was an independent prognostic factor of poorer overall survival and disease-free survival (p=0.017 and p=0.019, respectively). CONCLUSION: GLUT1 expression seems to play an important role in malignant transformation, and the glycolytic phenotype in invasive ductal carcinoma may indicate aggressive biological behavior and a worse prognosis.